What Predicts Students’ Academic Performance - Cholichul Hadi; Hung Chiao; Suen Mein-Woei; Dimas Agung Trisliatanto; Muh. Fitrah Ramadhan Umar (International Journal of Social Service and Research, 2022)
The Performance of a higher education institution was one of the important factors determining success in producing quality graduates. Academic achievement obtained by students was considered to the success of a student and the learning system at the institution. The academic quality was also inseparable from the background of the student itself. Besides, the system and climate of teaching and learning are created in the educational environment. This study aimed to describe students' academic Performance and the factors that influence the improvement in academic performance of undergraduate students majoring in Psychology at Airlangga University. This research used a quantitative approach with a descriptive survey research design. Based on the results of research conducted, it concluded that student performance, the program of study performance, and university performance on student's academic performance, both simultaneously and partially for undergraduate students at the Faculty of Psychology, Airlangga University.